CD19: a promising target for systemic sclerosis - Komura, Kazuhiro (Frontiers in Immunology, 2024)
Systemic sclerosis (SSc) is an autoimmune disease characterized by immune dysregulation, vascular damage, and fibrosis. B cells play a significant role in SSc through autoantibody production, cytokine secretion, and T cell regulation. Autoantibodies like anti-topoisomerase I and anti-RNA polymerase III are specific to SSc and linked to clinical features such as skin and lung involvement. B cell depletion therapies, particularly anti-CD20 antibodies like rituximab, have shown benefits in treating SSc, improving skin and lung disease symptoms. However, CD19, another B cell marker, is more widely expressed and has emerged as a promising target in autoimmune diseases. CD19-targeted therapies, such as CAR T cells and Uplizna® (inebilizumab), have demonstrated potential in treating refractory autoimmune diseases, including SSc. Uplizna ® offers advantages over rituximab by targeting a broader range of B cells and showing higher efficacy in specific patient subsets. Clinical trials currently investigate Uplizna ® 's effectiveness in SSc, particularly in severe cases. While these therapies offer hope, long-term safety and efficacy remain unknown. SSc is still a complex disease, but advancing B cell-targeted treatments could significantly improve patient outcomes and knowledge about the pathogenesis.